2014
DOI: 10.1111/risa.12211
|View full text |Cite
|
Sign up to set email alerts
|

A Multicriteria Decision Analysis Model and Risk Assessment Framework for Carbon Capture and Storage

Abstract: Multicriteria decision analysis (MCDA) has been applied to various energy problems to incorporate a variety of qualitative and quantitative criteria, usually spanning environmental, social, engineering, and economic fields. MCDA and associated methods such as life-cycle assessments and cost-benefit analysis can also include risk analysis to address uncertainties in criteria estimates. One technology now being assessed to help mitigate climate change is carbon capture and storage (CCS). CCS is a new process tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Five criteria, including economic cost, CO 2 emissions, SO 2 emissions, NO x emissions, and radioactive wastes, were analyzed over four different scenarios to choose the most flexible and robust strategy for power system planning. Choptiany and Pelot (97) proposed a multicriteria decision model for a carbon capture and storage risk problem. The model was developed to select CO 2 storage locations and to choose mitigation actions for reducing risks, considering the environmental, economic, and social impacts of the various options.…”
Section: Multicriteria Decision Makingmentioning
confidence: 99%
“…Five criteria, including economic cost, CO 2 emissions, SO 2 emissions, NO x emissions, and radioactive wastes, were analyzed over four different scenarios to choose the most flexible and robust strategy for power system planning. Choptiany and Pelot (97) proposed a multicriteria decision model for a carbon capture and storage risk problem. The model was developed to select CO 2 storage locations and to choose mitigation actions for reducing risks, considering the environmental, economic, and social impacts of the various options.…”
Section: Multicriteria Decision Makingmentioning
confidence: 99%
“…Multicriteria decision analysis (MCDA) is a familiar and well-tested method for taking a structured approach to the evaluation of risk, particularly for evaluating and ranking alternative solutions. Choptiany and Pelot (2014) and Choptiany et al (2015) apply the MCDA approach to CCS problems, such as choosing among competing CO 2 storage sites and optimising mitigation measures for risk reduction. The articles develop this approach for hypothetical coal-fired power plants involving post-combustion CO 2 capture, pipeline transport and storage in depleted oil reservoirs.…”
Section: Previous Attempts At Integrationmentioning
confidence: 99%
“…The decision model development has the standard MCDA features, including hierarchy of objectives, elicitation of utility functions, criteria weighting, scoring and sensitivity analysis. In Choptiany and Pelot (2014), the authors argue that this method enables an interactive engagement process with stakeholders who can participate as decision-makers in study process and can provide a "transparent assessment method by which to choose among competing projects." In Choptiany et al (2015) results further indicated functionality and positive responses from experts in government, environmental non-government organisations, research and industry who participated in the case study.…”
Section: Previous Attempts At Integrationmentioning
confidence: 99%
“…Meta-analyses of research activities relating to CCS have been conducted in the past. Choptiany et al [17] investigated articles with regard to the assessment of CCS projects under social, ecological, and economic criteria, while Choptiany and Pelot [18] developed an Multi Criteria Decision Analysis (MCDA) model for the systematic assessment of concrete CCS projects under these criteria. Zheng and Xu [19] reviewed CCS development trends by literature mining, and subsequently developed and examined a novel CCS technological paradigm (CCSTP) "to provide a guide for future CCS technological trends".…”
Section: Barriers Eu Com [5]mentioning
confidence: 99%